Perfil del microempresario y manejo crediticio de los microempresarios de la ciudad de Requena 2023 - Rengifo Mananita, Jakson (2024)
The objective of this research work is to determine the relationship between the profile of the microentrepreneur and the credit management of microentrepreneurs in the City of Requena 2023. Using the applied method, of non-experimental design, opting for a population of 50 merchants, who were A questionnaire was applied to them to collect information. The results showed that the microentrepreneur is not defined by gender, since there is no predominance between men and women who are dedicated to this activity, the majority have a committed age between 36 and 45 years with technical training and in free Union. Most have 1 to 3 employees and are dedicated to various unspecified areas. Although they do not receive training in person, your company has a team of trained human resources to carry out the necessary tasks. Regarding the credit management of microentrepreneurs, it was evaluated as regular, since they usually plan their expenses considering the payment of their loans, although they have a positive payment history and have had previous credits. However, they do not make financial projections to analyze the viability of their business and sometimes use credit responsibly by avoiding unnecessary personal expenses. Determining that there is a significant positive relationship between the profile of the microentrepreneur and their credit management (rh=0.633; p=0.000).